NONPURCHASED GOODWILL. - Walker, George T. (The Accounting Review, 1938)
Abstract Accountants, almost without exception, agree that goodwill should not be recognized in accounts until a bona fide purchase has been made. They are fully aware of the fact that goodwill created by a concern is just as valuable and in most instances, more valuable to that concern than to the firm which might make a specific purchase of that goodwill. Apparently there are a number of valid reasons which could be given in support of this position taken by accountants, other than the use of the term goodwill in connection with the watered stock frauds of the past. It is a generally accepted rule in accounting that it is the function of accounts to show the costs of assets, not the present value. This view may appear illogical at first sight. However, since an asset may have more than one value at a particular date, and since the actual cost of the asset to the organization is the only one which is capable of accurate determination, the latter, however, appears to provide a more realistic basis for the development of accounting principles, in spite of the fact that it encounters an obstacle in the situs of legal title.